Effects of D3 supplementation on ovulation in polycyctic ovarian syndrome (PCOS) patients - Al-Mosawi, Reyadh H.; Hamood, Nuha J. (International Journal of Psychosocial Rehabilitation, 2020)
Objectives: To explore the relation between vitamin D3 and ovulation in PCOS patients with vitamin D3 deficiency. Patients and Methods: 66 Patients were recruited from a private clinic in Karbala city / Al-Hindiya district. Criteria for selecting patients: aged 20-37 years, history of infertility, PCOS with low D3 blood level (